Deciphering Compositional Patterning in Plainware Ceramics from Late Prehistoric Hunter-Gatherer Sites in the Peninsular Ranges, San Diego County, California. Issue 4 (20th October 2013) - Quinn, Patrick S.; Burton, Margie M.; Broughton, David; Heymbeeck, Sophie Van
Abstract: We report on thin section petrographic analysis of plainware ceramic sherds from two Late Prehistoric hunter-gatherer sites in the Peninsular Ranges of San Diego County, California. We describe several distinctive compositional groups and compare these with previously analyzed ceramics and geological field samples to infer probable raw materials and provenance. In addition, taking into account archaeological and ethnohistoric context, we suggest cultural processes that may have contributed to the observed distribution across sites of three dominant compositional groups distinguishable within the general "brownware" category. The study demonstrates the potential of a compositional approach for investigating cultural practices among prehistoric hunter-gatherer populations with plainware ceramic craft traditions.